Kemampuan Pemecahan Masalah Matematika Siswa SMP dalam Menyelesaikan Soal HOTS Ditinjau dari Tahapan Polya - Zahrin Nurun Naim; Widya Putri Adianto; Azizah Miftakhul Jannah; Nur Rahmi Rusli (Mandalika Mathematics and Educations Journal, 2026)
This study aims to describe the mathematical problem-solving profile of junior high school students when solving Higher Order Thinking Skills (HOTS) problems based on Polya's stages. Employing a qualitative descriptive approach, this research involved 15 seventh-grade students from a high-performing public junior high school in Sleman Regency, Yogyakarta. The research instrument was an algebraic problem-solving test validated through expert judgment. The subjects were categorized into high, moderate, and low mathematical ability groups. Three students from each category were then selected for in-depth analysis using investigator triangulation. The results indicated that the high-category students successfully carried out all of Polya's stages, including implicit reviewing, as evidenced by procedural precision and accurate final answers. The moderate-category students were able to understand the problems but encountered errors during the execution stage and neglected to evaluate their results. Meanwhile, the low-category students experienced cognitive obstacles right from the problem-understanding stage and demonstrated no metacognitive activities. This study concludes that students' failure in solving HOTS problems is primarily caused by weak metacognitive control and an insufficient mastery of algebraic concepts. Consequently, mathematical instruction must habituate reflective strategies at every stage of the problem-solving process.